2015
DOI: 10.1002/srin.201500203
|View full text |Cite
|
Sign up to set email alerts
|

Transient Thermal‐Stress Analysis of Steel Slag Pots: Impact of the Solidifying‐Slag Layer on Heat Transfer and Wear

Abstract: The containers used for steel slag transportation to the recycling depot undergo hightemperature gradients and often deform plastically. Also, parts of the thereby solidified slag adhere to the pot walls, causing demolding problems and wear. A thorough finiteelement analysis of the heat transfer, initiated by filling the pots and essentially driven by radiation, and the thermal stresses is performed. Due to periodic fill-in and discharge, these are assumed to admit a quasi-stationary state referring to the pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…When studying the thermally stressed state of the motor-driven slag bowl, the peculiarities of the transition of slag from a liquid to a solid state were not taken into account, which is very carefully described in works [3,4]. Attention to the issue of determining temperature stresses at the boundaries of liquid and solid media was carefully consid-ered in [7,8]. Studies [8,9] report more specific measures regarding how the design of the bowl should be improved.…”
Section: Discussion Of Results Of Investigating the Thermal Stressed ...mentioning
confidence: 99%
See 3 more Smart Citations
“…When studying the thermally stressed state of the motor-driven slag bowl, the peculiarities of the transition of slag from a liquid to a solid state were not taken into account, which is very carefully described in works [3,4]. Attention to the issue of determining temperature stresses at the boundaries of liquid and solid media was carefully consid-ered in [7,8]. Studies [8,9] report more specific measures regarding how the design of the bowl should be improved.…”
Section: Discussion Of Results Of Investigating the Thermal Stressed ...mentioning
confidence: 99%
“…Paper [7] describes both analytical research results and experimental results using optical pyrometers. It is shown that the maximum temperatures when filling the cup reach 500 °С.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…1) belong to the group of massive and thick-walled casts. Their shaping microstructure (during crystallization) is significantly different from the castings with smaller dimensions, which in turn consequently can lead to elements segregation and shrinkage porosity [1][2][3][4][5][6][7]. Crystallization of heavy-section casting affects the final quality of cast iron castings, because off its wall thickness and longer cooling time.…”
Section: Introductionmentioning
confidence: 99%